Examining the Influence of Interpersonal Communication, Leadership Capability, Adaptability, and Excellence on Managerial Competence and Leadership Performance in Maritime Vocational Higher Education - Cahya Fajar Budi Hartanto; Yohanes Leonardus Sukestiyarno; Rusdarti Rusdarti; Abdurrahman Abdurrahman (International Journal of Pedagogy and Teacher Education, 2024)
Understanding how leadership moderates the effectiveness of maritime vocational higher education institutions is essential but underexplored. This study investigated the relationships between interpersonal communication, adaptability, capability, leadership excellence, managerial competence, and perceived leadership performance. A quantitative causal design was employed, collecting data through structured questionnaires from 145 lecturers at maritime vocational higher education institutions in Indonesia using purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to evaluate path coefficients and relationships between variables. The results indicate that interpersonal communication significantly influences perceived leadership performance but does not directly impact managerial competence. Conversely, leadership adaptability enhances both managerial competence and perceived leadership performance. Leadership excellence emerged as the most critical factor positively influencing both outcomes, while leadership capability demonstrated no significant direct effects on either. Additionally, managerial competence did not moderate the relationships between predictor variables and perceived leadership performance. These findings underscore the importance of fostering adaptability, communication, and leadership excellence in maritime vocational education. Tailored leadership development programs are necessary to cultivate these competencies among future leaders, enabling them to navigate the unique challenges of this sector. By focusing on these areas, institutions can prepare flexible, competent, and equipped leaders to enhance performance and managerial effectiveness in maritime education.